Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/ntr/ntv010
|View full text |Cite
|
Sign up to set email alerts
|

Use of Varenicline in Smokeless Tobacco Cessation: A Systematic Review and Meta-Analysis

Abstract: This pooled analysis suggests that varenicline is effective in achieving a 7-day point prevalence of SLT abstinence at 12 weeks but showed that this effect was not sustained at 26 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Fig 4 shows trends for ever waterpipe tobacco use. Various national and subnational surveys from the US documented absolute increases of between 0.3% and 3.1% per year[ 20 , 47 , 49 , 85 87 ]. Repeated rounds of a national school survey in Canada showed an absolute increase of 1.2% per year[ 55 57 ], and a similarly designed subnational study in Jordan reported an absolute increase of 7.3% per year between 2008 and 2011[ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 4 shows trends for ever waterpipe tobacco use. Various national and subnational surveys from the US documented absolute increases of between 0.3% and 3.1% per year[ 20 , 47 , 49 , 85 87 ]. Repeated rounds of a national school survey in Canada showed an absolute increase of 1.2% per year[ 55 57 ], and a similarly designed subnational study in Jordan reported an absolute increase of 7.3% per year between 2008 and 2011[ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies from 19 countries reported on ‘other’ defined prevalence measures[ 35 , 69 , 79 , 81 , 82 , 85 , 91 98 , 108 , 112 , 120 132 ], the details of which are presented in Table G in S1 File . Sixteen studies from ten countries did not specific the waterpipe prevalence measure[ 88 , 123 , 129 , 133 – 145 ], the details of which are presented in Table H in S1 File .…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-four reviews were identified that met eligibility criteria, including those among an unselected population of adults and those limited to a specific subgroup of adults (Table 1). Thirty-two reviews were designated as primary reviews . Eleven additional reviews had overlapping evidence with the primary reviews .…”
Section: Evidence For Adultsmentioning
confidence: 99%
“…Results of these reviews were consistent with the primary reviews in terms of effect magnitude and statistical significance and are not discussed further. Twenty-one reviews focused on specific subpopulations of adults (eg, people with severe mental illness, smokeless tobacco users) . These 21 reviews are not discussed here but are included in the full report…”
Section: Evidence For Adultsmentioning
confidence: 99%
“…Other reviews obtain similar results, 6,67 although one review found that effectiveness declines over time. 68 While studies show limited or no effects for nicotine replacement therapy, 6,66,67 an 8-week trial of 4-mg nicotine lozenge and tobacco-free snuff for 81 ST users with no immediate intention to quit found 12% biochemically-confirmed abstinence at week 26. 69 Reviews 6,66,67 have also found behavioral interventions, particularly telephone counselling or health care provider interventions, to promote quitting among ST users.…”
Section: Cessation Treatment Policiesmentioning
confidence: 99%